Aplikasi Perbandingan Sari Buah Duwet (Syzygium Cumini) Dan Air Dalam Pembuatan Jely Drink - Ayu Fatma Wati; Putu Timur Ina; I Made Sugitha (Master Program of Food Science and Technology, Faculty of Agricultural Technology, Udayana University, 2018)
The objective of this research were to observe the effect of java plum juice to the characteristic and appropriate treatment on jelly drink.The completely randomized design (CRD) with comparative treatment java plum juice and water six levels such us 10%:90%, 15%:85%, 20%:80%, 25%:75%, 30%; 70%, 35%:65% was use in the research. The data were analyzed through variance analysis and continued with Duncan`s Multiple Range Test (DMRT). The result showed that the ratio of java plum juice and water had a very significant effect to vitamin C, total anthocyanin, antioxidant activity (that IC50), color and texture (skor), color and taste (hedonic), and had a significant effect on flavor and texture (hedonic). Treatment of (35%:65%) the best characteristic of jelly drink, that give average value (vitamin C was 12,22 mg/100g, total anthocyanin was 4,87 mg/100g, antioxidant activity that determined by the value of IC50 was 96,24 mg/ml, color (purple) liked, taste (acid) rather liked, texture (mushy) plain, flavor plain, and overall acceptance rather liked) during storage at room temperature stability color of jelly drink decreased faster than that in refrigerator.